Financing of pharmaceutical assistance in the context of the Unified Health System from 2017 to 2022 (Research, Society and Development, 2024)
Objective: Map information about the financing of pharmaceutical assistance in the context of the Unified Health System. Method: This is a cross-sectional, analytical, descriptive study, taking as a time frame the period between 2017 and 2022, carried out through of Scope Review and the Siga Brazil Platform (Federal Budget) to consult the execution of expenses in budgetary actions in the field of Pharmaceutical Assistance and Strategic Inputs. Results: 33 articles were selected, out of 56 articles retrieved from the databases, including 12 case reports, 7 cross-sectional studies, 12 narrative reviews and 2 integrative reviews. It was found that the largest investment in the last six years was for the Specialized Component of Pharmaceutical Assistance, when compared to the Basic Component of Pharmaceutical Assistance and the Strategic Component of Pharmaceutical Assistance. Conclusion: Universal access to medicines by the public sector is still a major challenge. Your financing is still not enough. Finally, it is inferred that it is essential to review investments in the Basic Component of Pharmaceutical Assistance, improving access to medicines in Primary Health Care.